THE PURCHASE DECISION IN VIEW OF BRAND IMAGE, DESIGN AND DIVERSITY OF GLASSES PRODUCTS AT PRANOTO LAWEYAN OPTICS - Sanjaya, Muslichah Saskia; Mursito, Bambang; Kustiyah, Eny (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
The majority of individuals with vision difficulties prefer other solutions, primarily the use of glasses or contact lenses. The objective of the study is to investigate and analyze the impact of brand image, design, and product diversity on purchasing decisions at Pranoto Laweyan Optics. This research strategy combines descriptive and quantitative methodologies. The participants were all Pranoto Laweyan Optics customers. By mailing questionnaires using Google Form, 100 samples were collected using the approach of purposive sampling. This investigation employs the classical assumption test, the multiple linear regression test, the F-test, the T-test, and the determination coefficient test. Positive and major influences on purchasing decisions for glasses at Pranoto Laweyan Optics are brand image, design, and product diversity. The greater the brand's reputation, the variety of available designs, and the variety of products, the more they can influence customer buying decisions. Keywords: Brand Image, Design, Product Diversities, Purchasing Decisions